(untitled) - Pekka Jamsén (Rome, 1999)
This paper summarizes the main finding of a case study of capital formation and investment in a small sample of large coffee and dairy cooperatives in Kenya and provides some practical recommendations for improving capital formation in these two co-operative sectors
Keywords: agriculture and state,economics,kenya - economic policy